Business financing in Europe: How will higher interest rates affect companies' financial situation? - Daniel Bendel; Markus Demary; Michael Voigtländer (Institut der deutschen Wirtschaft (IW), 2017)
Companies' access to finance has a significant impact on their profitability and growth prospects. Without external financing, most firms are not able to invest, which is a prerequisite for economic growth. In contrast to the US, which has a capital market-based financial system, banks are the dominant lenders for firms in the euro area. Banking crises endanger access to finance. In the wake of the banking and sovereign debt crisis in the euro area, risk premiums for sovereign debt went up and spilled over to banking markets. Besides sovereigns, firms too faced credit constraints, especially in countries with presumably less sustainable public debt. After the European Central Bank (ECB) accelerated its accommodative monetary policy stance even further, interest rates for sovereigns and firms fell considerably, enabling firms to lend money at historically low rates. With the strengthened recovery of the euro area, the end of this ultra-low interest rate environment seems to be near, posing new challenges for firms in the euro area. The aim of this study is to analyse how firms have dealt with this changing financing environment in recent years and to what extent companies are ready for a change towards higher interest rates. To answer this research question, we have used data from the survey on the access to finance of enterprises (SAFE) provided by the ECB. We identify companies that are vulnerable to rising interest rates, as they will presumably encounter economic problems when financing costs rise. The percentage of vulnerable companies is extremely high in Greece (9.4 percent), Italy (8.5 percent) and France (5.7 percent). The lowest rate is in Germany (0.7 percent). In relation to the size of the national business sectors, 39 percent of all vulnerable firms are located in Italy, 23 percent in France and 15 percent in Spain. When the ECB starts to normalize monetary policy, these countries could be hit hard through their business sectors' vulnerability. As a comparatively many large companies are prone to the risk of rising interest rates in Portugal (4.0 percent of big Portuguese companies) and Greece (10.0 percent of big Greek companies), the labour markets in those countries could be disproportionally affected when interest rates rise too quickly or become too high.
Keywords: E32; E44; G30; 330